Age-related dynamics of sexual dimorphism in the structural components of physical performance in children aged 5-7 years - Dvorkina N.I. ,; Trofimova O.S. ,; Marinovich M.A. ,; Manakova Ya.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to evaluation of the expression of sexual differentiation in the physical abilities of children aged 5 to 7. Methods and structure of the study. Girls and boys aged from 5,5 to 6,0 years (n=28) and from 6,0 to 6,5 years (n= 28), respectively 6,5 to 7,0 years (n=20) and from 7,0 to 7,5 years (n=28), respectively, took part in the pedagogical experiment conducted on the basis of the Krasnodar Kindergarten No. 103 year (n=20). The following structural components of physical performance (PWC150) were subjected to statistical analysis: heart rate, body weight, body length, 10 squats in the first load, 20 squats in the second load and work power. Results and conclusions. It was discovered that in the annual changes of PWC150 in older preschoolers, compared to their initial measurements, in most cases, there were significant variations in the sexual differences between boys and girls aged 5,5 to 7,5. In the remaining components of PWC150, the initial differences between boys and girls aged 5,5 to 7,5 ranged from 0,91% to 5,71%. Therefore, the findings regarding the annual changes in the initial components of the physical performance of older preschoolers underscore the need for further investigation to determine the most effective approaches to physical education.